Influence of chlorine and rosemary essential oil postharvest pre-treatments on quality parameters of fresh tomatoes during storage - Caroline, Sibomana Imani; Leroy, Sado Kamdem Sylvain; Gustave, Mashugalusa Nachigera; Essia, Ngang Jean-Justin (Journal of Postharvest Technology, 2018)
Tomato is perishable and its high moisture content makes it susceptible for various postharvest losses. Tomato quality changes continuously after  harvesting, when fruits start lose quality because of environmental stress and pathogen infection. The study determined the effects of chlorine and  rosemary essential oil (REO) on the quality parameters and shelf life of fresh tomatoes during storage at ambient temperature. Tomatoes of uniform  shape and colour and free from pathogens were selected. Treatments were applied in a central composite design where chlorine (100, 200, 300 and  400 ppm of NaClO as hypochlorite of sodium), immersion time (1.5, 3, 4.5 and 6 minutes) and REO (200, 500, 700 and 1000 ppm) were factors  considered. Data were analysed through XLSTAT and STATISTICA. Results indicate that significant decrease in weight loss was observed where  there was increase in REO concentrations. All tomatoes converted towards full red independently of the factors from D10 of storage. Presence of  defects was observed with different intensity in treatments. Most fruits softened with the increase in fruit colour and storage time. Chlorine and REO  concentrations had an influence on the tomato flavour. There was extended shelf life of fruits since they were harvest at later stage for storage (light  red).
Keywords: Chlorine; Fruit quality; Rosemary essential oil; Shelf fife; Tomato